Are older long term care residents accurately prognosticated and consequently informed about their prognosis? Results from SHELTER study data in 5 European countries. - Maud Ten Koppel; Bregje D Onwuteaka-Philipsen; H Roeline Pasman; Roberto Bernabei; Iain Carpenter; Michael D Denkinger; Graziano Onder; Henriëtte G van der Roest; Eva Topinkova; Hein P J van Hout (PLoS ONE)
Background Informing residents in long term care facilities (LTCFs) about their prognosis can help them prepare for the end of life. This study aimed to examine which proportion of European LTCF residents, close to death, are accurately prognosticated and consequently informed about their prognosis; and to examine factors related to accurate prognostication and discussion of prognosis. Methods A subsample of SHELTER study data was used, consisting of: 500 residents from 5 European countries, who died within 6 months after their last assessment, and had a valid answer on the item 'End stage disease, 6 or fewer months to live'. This item was used to indicate whether an accurate prognosis was established and discussed with residents. Generalized estimating equations were used to examine factors related to establishment and discussion of accurate prognosis. Results 86.4% of residents close to death did not receive an accurate prognosis. Residents with cancer; fatigue; dehydration; and normal mode of nutritional intake were more likely to have an accurate prognosis established and discussed. Accurate prognostication and prognosis discussion was less likely for residents who: had a diagnosis under 'other'; initiated interactions; and residents from Germany, Italy and the Netherlands. Conclusions The great majority of residents close to death did not receive an accurate prognosis. Prognostication tools might help clinicians to increase their prognostic accuracy and communication training might help to discuss prognosis with residents.